(untitled) (Research, Society and Development, 2021)
In There are few simulation studies in the literature focusing on the production of biodiesel from vegetable oil deodorization distillate (VODD), a waste originating from the vegetable oil processing stage, using hydrotalcite-hydroxyapatite as a heterogeneous catalyst. In this study, the simulation process was performed using open interface software DWSIM® Version 6.3. The motivation relied on the positive performance of the catalyst during the experimental studies. So, in the simulator design, the lipid raw material, ethanol, and the catalyst were fed together in a CSTR-01 conversion reactor. The thermodynamic fluid package used for this process was the Non-Random Two-Liquid (NRTL) activity coefficient model. The process flowchart consisted of the reaction step (oil transesterification), and separation steps of the ethyl esters produced, excess ethanol and purification of biodiesel. As a result, different scenarios were simulated, using commercial soybean oil as a comparative form, different types of catalysts and different molar ratios of alcohol and VODD. Among the main differences between the simulated cases, it was demonstrated that the excess of alcohol (1:45) caused greater quantity of VODD consumption, and consequently the greater formation of ethyl esters (biodiesel), resulting higher conversions (> 95%). In addition, the results obtained confirmed the adequacy of VODD as a potential raw material to produce biodiesel, as it is relatively cheaper than edible oils and contributes to the use of waste. Thus, confirming that the chemical catalyst was able to form the main esters of fatty acids even using a residual raw material.